DAMPAK DISTRIBUSI PENDAPATAN PROGRAM “KHAS MATAB-AGRO ECO EDU WISATA” PADA PERTUMBUHAN EKONOMI INKLUSI: STUDI KASUS DI YSA BEDUGUL-BALI - Ely Mansur; Zeiniye; Abdullah Yaqin; Ni’matul Masruroh (Widya Balina, 2025)
This study aims to understand the impact of income distribution from the “Khas Matab–Agro Eco Edu Tourism” Program on the economic growth of communities in the area of the Al Hidayah Social Foundation (YSA), Bedugul, Bali. Unlike quantitative studies that measure impacts numerically, this research employs a descriptive qualitative approach to explore the perceptions, experiences, and socio-economic changes perceived by program beneficiaries. Data were collected through in-depth interviews, focus group discussions (FGDs), observation, and documentation. Thematic analysis was used to identify key themes related to changes in household income, consumption patterns, micro-enterprise empowerment, and perceptions of fairness in program distribution. The findings indicate that the “Khas Matab–Agro Eco Edu Tourism–Farming” Program not only enhances community economic access but also strengthens economic and social capital in education, fosters a sense of self-reliance, and promotes the sustainability of micro-enterprises. Nevertheless, challenges remain in ensuring equitable income distribution and improving community business management capacity. This study emphasizes the importance of an empowerment-based income distribution approach grounded in social capital theory (Putnam, 2000) and community empowerment theory (Chambers, 1997) for local economic development.